'A rhythm of another speech'. Pessoa's theory and practice of poetry translation. (1st October 2020) - Fischer, Claudia J.; Ferrari, Patricio
ABSTRACT: Fernando Pessoa devoted part of his prolific creative life to the practice of literary translation, mostly from his native Portuguese and English. He also wrote about this craft, as loose posthumous unfinished essays and scattered notes in his archive attest. Reading this material closely alongside a metrical analysis of selected published and unpublished poetry translations, we aim to: (1) understand the extent to which his thoughts on literary translation align with his poetry translation practice, primarily defined by his approach to poetic rhythm; (2) revisit some key ideas proposed by Wilhelm von Humboldt and Walter Benjamin on translation, as well as Plato's concept of anamnesis, all of which, arguably, resonate with Pessoa's poetry translation theory and practice. The article also includes critical transcriptions of unpublished material from Pessoa's Archives held at the National Library of Portugal (Pessoa's Papers) and the Fernando Pessoa House (Pessoa's Private Library), both located in Lisbon.